Preliminary study of the distribution and risk assessment of mercury in different surficial sediments along the coastal area of the province Thai Binh in Vietnam. Issue 1 (1st January 2020) - Duong, Thi Lim; Nguyen, Thi Lan Huong; Nguyen, Thi Hue; Nguyen, Thi Huong Thuy; Tran, Thu Thuy; Nguyen, Van Long; Walenzik, Gabriele; Genthe, Wolfgang; Rudolph, Karl-Ulrich; Pham, Ngo Nghia; Dao, Ngoc Nhiem
ABSTRACT: Surficial sediment samples along the coastal area of the province Thai Binh in Vietnam have been collected and analysed by modified Tessier method for the mercury content. The mercury levels in these samples were found in the range between 0.12–3.79 mg/kg. Elevated concentrations were observed in some locations close to tidal marshes, large aquaculture productions or low-lying areas. The highest level of mercury was detected in a low-lying terrain near large aquaculture productions. The majority of the mercury species in all samples were witnessed in the fraction bound to organic matters. The predominance of this fraction is possibly associated with some misuses of mercurial fungicides by aqua farmers. These mercury species remain quite resistant in the sediments, thus posing a quite low risk for the surrounding ecological environment. Nevertheless, it is necessary to undertake further studies to evaluate the effect of this contamination on the food chain.